Modernization of Tax Administration, Human Integrity and Taxpayer Compliance in East Preanger - Pratiwi, Laras; Somantri, Yeni Fitriani (AIBPM Publisher, 2021)
East Preanger is one of the regions in Indonesia that has a high economic potential. The potential economic in East Preanger based on knowledge and culture. Unfortunately, awareness of paying taxes still a serious spotlight. Tax revenue at the maximum level can be realized if people obey on their tax obligations. Some of the factors that cause low taxpayer compliance are the existence of public dissatisfaction with public services, uneven infrastructure development, and the many corruption cases committed by unscrupulous officials. This research is an associative study, which aims to determine the influence of tax modernization and human integrity on taxpayer compliance. Sampling technique using accidental sampling with the number of respondents 61 individual taxpayers scattered in the East Prianger. The results showed that tax modernization had no effect on taxpayer compliance, while human integrity had an effect on taxpayer compliance. This research is important because it’s able to explain the factors that affect taxpayer compliance. The novelty in this study is focusing on human integrity on tax compliance, especially in the East Preanger region. This study also provides ideas about solutions that must be taken by the government and society to increase tax revenue, especially in the East Prianger.